MANGROVES UTILIZATION, DEPENDENCY AND MANAGEMENT: THE CASE OF CARMEN, CEBU, PHILIPPINES - Delan, Gloria; Vivas-Rica, Rachel Luz P; Piquero, Alfonso S; Corrales, Christine M; Lapag, Tony L; Pepito, Ador R (Journal of Agriculture and Technology Management; Tropical Technology Journal Volume 18 No. 1, 2015, 2015)
A survey on mangrove dependency, awareness, utilization and management was conducted in the coastal barangays of Carmen, Cebu. Results revealed that gleaning and fishing are major activities in the mangrove areas. Coastal communities are dependent on mangroves for subsistence where most of their catch are for home consumption. Locals perceived the importance of mangroves because of their knowledge that it serves as breeding, feeding and nursery grounds for many estuarine and marine organisms as well as protect the coast against erosion and big waves. Coastal communities are very much satisfied with the strict implementation of policies in the conservation and protection of their mangrove resources.